Curriculum Development in Islamic Educational Institutions: A Case Study at Madrasah Tsanawiyah Negeri 1 Pati - Achyar Auliya Shofa; Mudofir Mudofir; Imam Makruf (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study analyzes curriculum development at MTsN 1 Pati in implementing the Independent Curriculum, with particular attention to the integration of Islamic values and digital literacy. Non-participant observation, semi-structured interviews, and documentation including the vice principal for curriculum, teachers, and curriculum-related documents were used to gather data using a naturalistic qualitative approach. Through reduction, display, verification, and conclusion drawing, data were studied interactively. The results demonstrate that updating the madrasah's vision and mission is part of curriculum development at MTsN 1 Pati, strengthening its religious culture, and establishing flagship programs such as the Boarding School and Digital Class. The curriculum integrates Islamic values, digital literacy, technological competence, and global skills through intracurricular, co-curricular, and extracurricular activities. These efforts contribute not only to students’ academic achievement but also to character formation in accordance with Islamic educational principles. However, several challenges remain, including teachers’ readiness to implement differentiated learning, variations in student motivation, changes in learning paradigms, and technical limitations related to digital technology. The study emphasizes the necessity of strong institutional support, sufficient technology infrastructure, and ongoing professional development for teachers. In order to show that madrasahs can adjust to educational reform while preserving their Islamic identity and unique educational features, this research proposes a curriculum integration model that integrates religious values and digital literacy within the Independent Curriculum framework.